The effect of artificial lure type and environment conditions on the short-time post-release mortality of two recreational fished Luciobarbus species - Atessahin, Tuncay (Wiley, 2022)
This study investigated the relationship between (artificial) lure types and catches of undersized Luciobarbus mystaceus and Luciobarbus esocinus and examined their short-time post-release mortality at the Keban Dam Lake, Eastern Turkey. A total of nine lure types included three different sizes: 3, 4, and 5 cm, and each had either blue, red, or yellow colour were used. A significant relationship was detected between the lures size and the size structure of both fishes caught from the Keban Dam Lake. The larger lure (5) was significantly more efficient to avoid the catch of undersized fishes (legal size >= 50 cm total length), corresponding to 31.3% in L. mystaceus and 3.2% in L. esocinus. Also, a significant relationship was detected between the lures' colour and the size structure of L. mysteceus though this relationship was not significant in L. mysteceus. The blue and yellow lures caught larger size fishes than the red lure. The short-time post-release mortality was observed in smaller size fishes closer to the legal minimum lengths. The lure size 4 caused the highest short-time post-release mortality frequently hooked in the gills and upper-lower jaws. The findings of this study recommended using lures with a hook size of 5 cm to minimise catches of undersized fish with the least chances of short-time post-release mortality.
Keywords: bait; catch-and-release; hook selectivity; Keban Dam Lake; Luciobarbus esocinus; Luciobarbus mystaceus; recreational fisheries